One-Month Follow-Up of Patients with Unspecified Abdominal Pain Referring to the Emergency Department; a Cohort Study - Hoseininejad, Seyed Mohammad; Jahed, Reza; Sazgar, Mohammad; Jahanian, Fatemeh; Mousavi, Seyed Jaber; Montazer, Syed Hosein; Asadi, Touraj; Aminiahidashti, Hamed (Archives of Academic Emergency Medicine, 2019)
Introduction: About one third of patients referring to emergency department (ED) with abdominal pain, are discharged without a definite diagnosis. This study aimed to investigate the one-month outcome of patients with unspecified abdominal pain. Methods: This cohort study was conducted on subjects who were evaluated in ED with unspecified abdominal pain and were referred to the gastroenterology clinic and followed for one month. Finally, they were divided into two groups of cases with clear cause of abdominal pain and unclear cause of abdominal pain and patients’ characteristics were compared between the groups. Results: 150 cases with the mean age of 40.68 ± 18.34 years were studied (53.3% female). After one month, 67 (44.7%) patients still complained of abdominal pain. A definitive cause of abdominal pain was established in 88 (58.7%) cases. There was not any significant difference between groups regarding, sex distribution (p = 012), duration of pain (p = 0.11), history of previous similar pain (p = 0.136), pain radiation (p = 0.737), length of hospital stay (p = 0.51), and presence of anorexia (p = 0.09), nausea and vomiting (p= 0.50), fever (p = 1.0), diarrhea (p = 0.23), and constipation (p = 0.07). There was a significant difference between the groups regarding location of pain (p = 0.017), age (p = 0.001) and history of comorbid diseases (p = 0.046). The predictive factors of finding a clear cause for abdominal pain in one-month follow-up, were leukocytosis (OR: 5.92 (95% CI: 2.62 – 13.39); p < 0.001), age (OR: 2.78 (95% CI: 1.15 – 6.71); p = 0.023), and outpatient follow-up (OR: 1.04 (95% CI: 1.02 – 1.07); p < 0.001). Conclusion: Approximately, 40% of patients who were discharged with unspecified abdominal pain did not receive a clear diagnosis after one month of follow-up. Older age, leucocytosis in initial evaluations, and outpatient follow-up increased the probability of finding a clear cause for abdominal pain in the mentioned cases.